Median nerve stimulation induced motor learning in healthy adults: A study of timing of stimulation and type of learning. (9th July 2018) - Carvalho, Sandra; French, Melanie; Thibaut, Aurore; Lima, Wilrama; Simis, Marcel; Leite, Jorge; Fregni, Felipe
Abstract: Median nerve stimulation (MNS) has been shown to change brain metaplasticity over the somatosensory networks, based on a bottom‐up mechanism and may improve motor learning. This exploratory study aimed to test the effects of MNS on implicit and explicit motor learning as measured by the serial reaction time task (SRTT) using a double‐blind, sham‐controlled, randomized trial, in which participants were allocated to one of three groups: (a) online active MNS during acquisition, (b) offline active MNS during early consolidation and (c) sham MNS. SRTT was performed at baseline, during the training phase (acquisition period), and 30 min after training. We assessed the effects of MNS on explicit and implicit motor learning at the end of the training/acquisition period and at retest. The group receiving online MNS (during acquisition) showed a significantly higher learning index for the explicit sequences compared to the offline group (MNS during early consolidation) and the sham group. The offline group also showed a higher learning index as compared to sham. Additionally, participants receiving online MNS recalled the explicit sentence significantly more than the offline MNS and sham groups. MNS effects on motor learning have a specific effect on type of learning (explicit vs. implicit) and are dependent on timing of stimulation (during acquisition vs. early consolidation). More research is needed to understand and optimize the effects of peripheral electrical stimulation on motor learning. Taken together, our results show that MNS, especially when applied during the acquisition phase, is a promising tool to modulate motor leaning. Abstract : Our results show that during the last trials of the retest phase, the group that received MNS during acquisition and consolidation phases showed an increased learning index for the explicit sequence when comparing to sham.